Are Psychotic Experiences Related to Poorer Reflective Reasoning? - Mækelæ, Martin J.; Moritz, Steffen; Pfuhl, Gerit (Frontiers in Psychology, 2018)
Background: Cognitive biases play an important role in the formation and maintenance of delusions. These biases are indicators of a weak reflective mind, or reduced engaging in reflective and deliberate reasoning. In three experiments, we tested whether a bias to accept non-sense statements as profound, treat metaphorical statements as literal, and suppress intuitive responses is related to psychotic-like experiences. Methods: We tested deliberate reasoning and psychotic-like experiences in the general population and in patients with a former psychotic episode. Deliberate reasoning was assessed with the bullshit receptivity scale, the ontological confabulation scale and the cognitive reflection test (CRT). We also measured algorithmic performance with the Berlin numeracy test and the wordsum test. Psychotic-like experiences were measured with the Community Assessment of Psychic Experience (CAPE-42) scale. Results: Psychotic-like experiences were positively correlated with a larger receptivity towards bullshit, more ontological confabulations, and also a lower score on the CRT but not with algorithmic task performance. In the patient group higher psychotic-like experiences significantly correlated with higher bullshit receptivity. Conclusion: Reduced deliberate reasoning may contribute to the formation of delusions, and be a general thinking bias largely independent of a person’s general intelligence. Acceptance of bullshit may be facilitated the more positive symptoms a patient has, contributing to the maintenance of the delusions.